Strategi Pemasaran Digital Dalam Mempertahankan Bisnis Knalpot NDK Exhaust Masa Pandemi Covid-19 (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
Abstract Industry is used as a part of economic production that is focused on certain manufacturing processes that must have large capital before it can make a profit. Indonesia is one of the largest automotive bases in the Southeast Asia region to date. One of the automotive products in Indonesia is racing exhaust. . Racing exhaust is one part of a vehicle or tool that is installed with the aim of being a drain access channel, usually found on motorized vehicles and cars. A racing exhaust craftsman is someone who makes exhaust from raw (unfinished) materials into ready-to-use/sold goods. However, it cannot be denied, the more racing exhaust craftsmen, the greater the competition in production. Due to the COVID-19 pandemic, several problems have occurred in the racing exhaust industry. However, the problem does not affect the income of the NDK Exhaust Purbalingga exhaust industry. While exhaust craftsmen complained that their income had decreased due to problems in the midst of the covid-19 pandemic, NDK Exhaust Purbalingga actually increased their income, even being able to market their products overseas. This is because NDK Exhaust has implemented a 4 P marketing system, namely product, price, place, and promotion. And actively promote on e-commerce. Keywords : business resilience, e-commerce, marketing strategy,